Pengaruhhearning Per Share, Debt To Equith Rasio, Pertumbuhan Penjualan, Dividen, Return On Equith, Current Rasio Terhadap harga Saham Pada perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia 2016-2019 - Ena Betina Br Tarigan; Mesrawati Mesrawati; Melda C Silaban; Agustina Sibaran; Fedrico Juventus Samosir (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aims to analyze how the influence of Earning Per Shere (EPS), Debt To Equith Ratio (DER), Sales Growth (PP), Dividends, Retrun On Equith (ROE), Current Ratio (CR), on Share Prices in Registered ConsumereGoods Companies. on the Indonesia Stock Exchange 2016-2019. Partially or simultaneously, researched based on 42 populations with 26 sample companies and 104 total data studied. From the conclusion we can know that the influence between EPS is not significant and has no effect on stock prices, DER has no impact and is not relevant to stock prices. PP has no and insignificant effect on stock prices, dividends have no impact and is irrelevant to share prices, ROE has no and insignificant effect on stock prices on stock prices, CR has no effect and is not relevant to share prices. This conclusion was generated through the F test with research conducted using the SPSS 20 program and through the Multiple Linear Analysis method. Keywords: Earning Per Shere (EPS), Debt To Equith Ratio (DER), Sales Growth (PP), Dividends, Retrun On Equith (ROE), Current Ratio (CR), Stock Price.